Gum Arabic: A Commodity with Versatile Formulations and Applications - Shaymaa A. Mohamed; Asmaa M. Elsherbini; Heba R. Alrefaey; Kareem Adelrahman; Alshaimaa Moustafa; Nishal M. Egodawaththa; Kaitlyn E. Crawford; Nasri Nesnas; Sally A. Sabra (Nanomaterials)
Gum Arabic (GA), or acacia gum, refers to the dried exudate produced by certain Acacia trees. GA is composed mainly of a mixture of polysaccharides and glycoproteins, with proportions that can slightly differ from one species to another. It is commonly utilized in the food and pharmaceutical industries as a stabilizer or an emulsifier owing to its biocompatibility, hydrophilicity, and antibacterial properties. In addition, GA can be manipulated as it possesses many functional groups that can be used in grafting, cross-linking, or chemical modifications to add a new feature to the developed material. In this review, we highlight recent GA-based formulations, including nanoparticles, hydrogels, nanofibers, membranes, or scaffolds, and their possible applications in tissue regeneration, cancer therapy, wound healing, biosensing, bioimaging, food packaging, and antimicrobial and antifouling membranes.